Tuning Halide Composition allows low dark current perovskite photodetectors with high specific detectivity - Furlan,F; Nodari,D; Palladino,E; Angela,E; Mohan,L; Briscoe,J; Fuchter,MJ; Macdonald,TJ; Grancini,G; McLachlan,MA; Gasparini,N (Advanced Optical Materials, 2022)
Tuning halide composition in perovskites is a powerful approach demonstrated to enhance the performance of perovskite photovoltaic devices where such compositional modifications drive improvements in open-circuit voltage (Voc) and a reduction in nonradiative voltage losses. Similarly, photodetectors (PDs) operate as light to current conversion devices hence it is relevant to investigate whether performance enhancements can be achieved by similar strategies. Herein, perovskite PDs are fabricated with an inverted photodiode configuration based on a MAPb(I1-xBrx)3 perovskite (MA = methylammonium) active layer over the x = 0–0.25 composition range. Interestingly, it has been found that increasing the Br content up to 0.15 (15%) leads to a significant reduction in dark current (Jd), with values as low as 1.3 × 10−9 A cm−2 being achieved alongside a specific detectivity of 8.7 × 1012 Jones. Significantly, it has been observed an exponential relationship between the Jd of devices and their Voc over the 0–15% Br range. The superior performances of the 15% Br-containing devices are attributed to the reduction of trap states, a better charge extraction of photogenerated carriers, and an improvement in photoactive layer morphology and crystallinity.